Synthesis and Characterization of Zn/Al, Zn/Fe, and Zn/Cr Layered Double Hydroxides: Effect of M3+ ions Toward Layer Formation - Palapa, Neza Rahayu; Saria, Yosi; Taher, Tarmizi; Mohadi, Risfidian; Lesbani, Aldes (Science and Technology Indonesia, 2019)
Layered double hydroxides are composed by substitution of metal cation divalent and trivalent. Metal cation divalent and trivalent can be changed. In this work, effect metal cation trivalent (M3+) toward layer formation were studied. Synthesis of LDHs has used co-precipitation methods with molar ratio 3:1 and kept pH at 10. The result of synthesis was characterized by X-ray Diffraction (XRD) and Fourier Transform Infrared (FT-IR) analyses.